Stabilization of cytokine mRNAs in iNKT cells requires the serine-threonine kinase IRE1alpha - Srinath Govindarajan (Nature Portfolio, 2018)
Invariant natural killer T (iNKT) cells rapidly enhance cytokine secretion and effector function following activation, but the underlying mechanism is still unclear. Here the authors show that an endoplasmic reticulum stress sensor, inositol-requiring enzyme 1α, activates the p38 kinase to stabilize cytokine mRNA for enhanced iNKT functions.